KOMUNIKASI PARTISIPATIF DALAM PROGRAM PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA (Kasus di Desa Dayah Tanoh Kecamatan Mutiara Timur Kabupaten Pidie Provinsi - Elly Susanti (JURNAL AGRIBISNIS TERPADU, 2015)
The emerging paradigm of participatory development communication emphasizes participation andinvolvement from planning to decision-making process. PEKKA promotes the concept trough bottomupinitiative including planning, implementation and project evaluation. This study aims to investigateprocess of participatory development communication by PEKKA and economic empowerment ofwomen household. The research employs a case study of Desa Dayah Tanoh, Kecamatan MutiaraTimur, Kabupaten Pidie, Aceh Province. Data gathering was through fieldwork and in-depthinterviews in April-May 2012. The research finds that PEKKA’s approach provides an equalopportunity and access to the beneficiaries by using monologue, dialogue and combination of bothchannels. Several factors such as age, education, occupation, marital status, number of familydependent, family support, institutional support and role of field assistant contribute to efficacy ofparticipatory communication. Furthermore, the effectiveness of the strategy is a factor of successful ofthe project that is women economic empowerment.